Conductivity Maxima Vs. Temperature: Grotthuss Conductivity in Aprotic Molten Salts. (30th August 2016) - Aravindakshan, Nikhil P.; Kuntz, Colin; Gemmell, Kyle; Johnson, Keith; East, Allan
Abstract : The phenomenon of electrical conductivity maxima of molten salts versus temperature during orthobaric (closed-vessel) conditions is further examined. First, we summarize results from density-functional-based molecular dynamics simulations of molten SnCl2 and HgBr2, which provided structural information but also succeeded in reproducing (i) previously published experimental conductivities to within an order of magnitude, and (ii) the conductivity maxima. The "hopping" mechanism we previously proposed is now termed a Grotthuss mechanism, which became quite clear in the simulations of the molecular liquid HgBr2 which exhibited Grotthuss chains of bromide transfers. Second, we fit the experimental conductivities of 12 different molten salts with the equation, which fits well in most cases, and mapped the density-dependent Arrhenius equation onto it in a particular way, generating A and Ea curves for each molten salt for physical insight.